ChemInform Abstract: Microwave Assisted Azide—Alkyne Cycloaddition Reaction Using Polymer Supported Cu(I) as a Catalytic Species: A Solventless Approach. Issue 42 (October 2015) - Taher, Abu; Nandi, Debkumar; Islam, Rafique Ul; Choudhary, Meenakshi; Mallick, Kaushik
Abstract Newly synthesized polymer supported copper(I) composite is used as an effective catalyst for a 1, 3‐dipolar cycloaddition reaction between terminal alkynes and azides to synthesize 1, 2, 3‐triazoles with excellent yields using a microwave irradiation technique in the absence of any solvent.